Genotoxicity evaluation of metformin and glimepiride by micronucleus assay in exfoliated urothelial cells of type 2 diabetes mellitus patients. (September 2015) - Harishankar, M.K.; Logeshwaran, S.; Sujeevan, S.; Aruljothi, K.N.; Dannie, M.A.; Devi, A.
Abstract: Micronucleus (MN) assay was performed on the exfoliated urothelial cells to detect the genotoxic effects of the anti-hyperglycemic drugs, metformin and glimepiride in T2DM patients and to use it as a biomarker for DNA damage by assessing the frequency of micronuclei in the exfoliated urothelial cells. A total of 201 subjects (147 T2DM patients & 54 Normal cases) were selected from diverse age groups (25–75 years) and the mean MN frequency was examined per 1000 cells in all the subjects. Relative to the control group (5.02 ± 1.01), an increased MN frequency was observed in females (26.15 ± 2.15) when compared to males (23.08 ± 2.09) in T2DM patients. Further analysis showed that there was a profound increase in the number of MN in the patients using metformin alone (23.02 ± 4.44), or combination of metformin & glimepiride (24.98 ± 2.87) than to the subjects using glimepiride alone (17.52 ± 3.28). It has been proven by this simple, reliable and non-invasive method that metformin has a potential role in causing genotoxicity and that the MN observed in exfoliated urothelial cells could be used as a reliable biomarker in monitoring the genotoxic risk of the anti-hyperglycemic drugs. Highlights: MN assay in urothelial cells is a reliable method for detection of cytogenetic damage. Increased MN frequency in T2DM patients treated with metformin and glimepiride. Female patients have an increased MN frequency compared to males. Duration of the drugs doesn't have significant effect on genotoxicity.